2007
DOI: 10.1065/espr2006.11.361
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and Biovolatilization of Arsenic by Heat-Resistant Fungi (5 pp)

Abstract: . Biovolatilization and biosorption have a great potential for bioremediation of contaminated localities. However, results showed that not all fungal species are effective in the removal of arsenic. Thus, more work in this research area is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…4 -7 times higher than that of Penicillium sp. However, Cernanský et al [8] indicated that when the initial As content in a culture system was 2500 lg, which is equal to 50 mg/L As, Aspergillus clavatus bioaccumulated 736.0 lg As and biovolatilized 1522.0 lg As during a 30-day cultivation period. The abilities for As bioaccumulation and biovolatilization of various microbial strains are very variable, and parameters such as the cultivation period, initial As content, and other environmental factors may affect the efficiencies of As bioaccumulation and biovolatilization to some extent.…”
Section: Bioaccumulation and Biovolatilization Of Pentavalent Arsenicmentioning
confidence: 98%
See 2 more Smart Citations
“…4 -7 times higher than that of Penicillium sp. However, Cernanský et al [8] indicated that when the initial As content in a culture system was 2500 lg, which is equal to 50 mg/L As, Aspergillus clavatus bioaccumulated 736.0 lg As and biovolatilized 1522.0 lg As during a 30-day cultivation period. The abilities for As bioaccumulation and biovolatilization of various microbial strains are very variable, and parameters such as the cultivation period, initial As content, and other environmental factors may affect the efficiencies of As bioaccumulation and biovolatilization to some extent.…”
Section: Bioaccumulation and Biovolatilization Of Pentavalent Arsenicmentioning
confidence: 98%
“…Furthermore, a literature search on all reported fungi capable of As bioaccumulation and/or biovolatilization, such as Scopulariopsis brevicaulis [7], Phaeolus schweinitzii [6], Penicillium sp. [13], Fusarium oxysporum [12] Neosartorya fischeri, Aspergillus niger, Eupenicillium cinnamopurpureum, Talaromyces wortmannii, Talaromyces flavus, Penicillium glabrum, Aspergillus clavatus, Trichoderma viride [8,9], etc., it is seen that this is the first report of such data for T. asperellum and P. janthinellum in this study.…”
Section: Bioaccumulation and Biovolatilization Of Pentavalent Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effect of initial pH (2-10) on arsenic uptake by rice polish, sorption experiments were performed by using 50 mL of solution with initial arsenic concentration [As(III) and As(V)] of 1000 g/L and adsorbent dose of 20 g/L at temperature 20 • C. Effect of variation of initial metal ion concentration and contact time was studied with an initial arsenic concentration of 100, 500 and 1000 g/L and rice polish of 20 g/L; pH was kept at 7 for As(III) and at 4 for As(V) and contact time was varied from 10 to 150 min at 20 • C. The effect of temperature (20,30 and 40 • C) on arsenic uptake was studied at initial arsenic concentrations of 1000 g/L and adsorbent dose of 20 g/L at pH 7 for As(III) and 4 for As(V).…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%
“…At this juncture advances in the knowledge of biosorption has gained important credibility during recent years because of its ecofriendly nature, excellent performance, and low cost domestic technique for remediating even heavily metal loaded water [15]. Various biosorbents have been reported for efficiently accumulating arsenic from water [1,13,14,[16][17][18][19][20][21]. However, there still lies a strong challenge in developing biosorbents for arsenic removal with high uptake efficiency, low cost and well-elucidated sorption mechanism.…”
Section: Introductionmentioning
confidence: 98%